2013
DOI: 10.1039/c3nr02416d
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanowires as effective luminescent sensing materials for nitroaromatic derivatives

Abstract: We report on the efficient room-temperature photoluminescence (PL) quenching of ZnO in the presence of 2,4-dinitrotoluene (DNT) vapor and for concentration as low as 180 ppb. Compared to ZnO thin films, ZnO nanowires exhibit a strong (95%) and fast (41 s) quenching of the PL intensity in the presence of DNT vapor. Assuming that the PL quenching is due to a trapping of the ZnO excitons by adsorbed DNT molecules, Monte-Carlo calculations show that the nanometric dimensions as well as the better crystallographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 30 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…ZnO‐based gas sensors have been applied in many fields to detect trace analytes, such as, ethanol, urea, and TNT . A ZnO nanorod‐based chemiresistor sensor shows good sensitivity toward trace (down to few ppb) DNT and TNT molecules . However, the most leading ZnO nanostructure‐based chemiresistor explosive sensors only have limited responses, such as, 20% toward 60 ppb TNT vapor .…”
Section: Introductionmentioning
confidence: 99%
“…ZnO‐based gas sensors have been applied in many fields to detect trace analytes, such as, ethanol, urea, and TNT . A ZnO nanorod‐based chemiresistor sensor shows good sensitivity toward trace (down to few ppb) DNT and TNT molecules . However, the most leading ZnO nanostructure‐based chemiresistor explosive sensors only have limited responses, such as, 20% toward 60 ppb TNT vapor .…”
Section: Introductionmentioning
confidence: 99%
“…The first one, which corresponds to the high peak located at the lower wavelength (around 380 nm), is associated to the near-band edge emission of the material. This strong emission corresponds to the recombination of electrons from the minimum of the conduction band with holes of the valence band of the semiconducting ZnO 25,26 . Additionally, by zooming in the visible light region of the spectra (see the inset in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sensing surface can be easily enlarged by coating the polymer layer on non-planar surfaces. The enlarged sensing surface leads to gain in sensitivity due to the increased probability of analyte adsorption [15]. The approach was tackled by Zhu et al whom showed that coating a FSP on arrays of aligned ZnO nanorods allowed for better response time and quenching efficiency while having higher polymer fluorescence when compared to a polymer layer coated on a standard quartz plate [16].…”
Section: Materials and Conceptmentioning
confidence: 99%
“…The growth process by which the ZnO thin films were obtained is detailed in [19]. It is important to stress that most of the fluorescent polymers which are used for explosive chemosensing applications are excited by UV-blue light [9,10,11,12,13,14,15,16,22]. Thus, ZnO is not only adequate for exciting the FSP studied herein, but also adequate for most of the studied FSPs.…”
Section: Materials and Conceptmentioning
confidence: 99%